Penggunaan Instagram untuk Meningkatkan Pemasaran UMKM Batik - Fauzi, Anis; Mashuri, Imam; Nasrodin, Nasrodin; Faishol, Riza; Muttaqin, Ahmad Izza; Zunita, Ratna (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
Currently, the marketing and sales of UMKM products, especially the Batik Home Industry UMKM in Macanputih Village, are still conducted traditionally, relying solely on orders from local residents, such as nearby government institutions, educational institutions, and banks. The Covid-19 pandemic has had an extraordinary impact on various sectors, especially the economy, resulting in many institutions, educational facilities, and others being in lockdown or not operating as usual. Additionally, the batik production activities in Banyuputih hamlet are on a small scale, and the wider public is not aware of them. This method has not been optimal in delivering information, as it cannot reach the broader community, particularly the residents of Banyuwangi Regency. This mentoring and research aim to utilize Instagram social media as a form of modern marketing communication. By leveraging Instagram, the most popular and sought-after modern marketing communication tool, the goal is to facilitate consumers in making purchases or transactions and easily finding information about the products they intend to buy, thereby increasing the sales volume of UMKM actors.